Was Theresa May a One Nation Conservative? - Raphaële Espiet-Kilty (Revue Française de Civilisation Britannique)
It took the Conservative Party seventy-eight years to come to a final decision as to what Disraeli’s vision of One Nation formally signified. By that time, One Nation Conservatism had already been elevated to the status of political myth with many endowing it with much more meaning than it may actually have had. What the 1950 Pamphlet put forward was a far cry from the progressive, let-alone ‘left-wing’, Toryism which was putatively promoting a more equal nation in which a whole people, united by a spirit of solidarity, would forge ahead as one. The Pamphlet reflected the differences between 1950s’ Britain and Disraeli’s conceptions, and how the Conservative Party was adapting to the changes. It revealed divisions even amongst its authors and the One Nation Group that was subsequently formed, notably over economic policies. Be that as it may, influenced by a certain Disraelian spirit of noblesse oblige, conferring a moral duty to look after the weaker and less privileged in society, One Nation Conservatives accepted that, for the sake of social peace, it was the responsibility of a Conservative government to promote social harmony and preserve the capitalist order which delivered economic growth. From then on, One Nation Conservatism became increasingly associated with a group of high-profile Conservatives who, from Lord Hailsham to Iain MacLeod and Edward Heath, contributed to its reputation as socially paternalistic, Europhile, economically interventionist (its most controversial aspect) and generally favourable to a strong United Kingdom acting as one nation. This was a ‘big state’ Conservatism that was prepared to intervene to spur the development of a Britain that would provide opportunities for all across the UK.Some sixty years later, to distance himself from the toxic legacy of Thatcherism – the so-called antithesis to ‘big state’ One nation Conservatism – David Cameron claimed to be a One Nation Conservative, thus reactivating a qualifier that had not been used for over forty years. Theresa May did likewise, albeit indirectly, announcing that ‘David has led a One-Nation government, and it is in that spirit that I also plan to lead’ (T. May, 13 July 2016). Unlike Cameron however, she was not a member of the One Nation Group. And yet, I will argue that from the launch of her leadership campaign in 2016 to the publication of the 2017 Conservative Party Manifesto, she was consistently more attuned to the One Nation tradition than either Cameron or, arguably, Johnson, who, on succeeding May, would also declare that his government was One Nation. May was a complex political figure who came to power in extremely difficult circumstances, notably with regard to the negotiations taking place on Britain’s exit from the European Union. May’s One Nation Conservatism would become the first victim of a combination of bad decisions, of a lack of conviction and clarity, and of extreme tensions within the party and the government over Brexit. The second victim would be May herself.